Participação do sistema colinérgico em comportamentos socialmente motivados - Ana Cláudia Schneider Raslan (2011)
Acetylcholine (ACh) modulates cognition, such learning, as memory and attention. However, little is known about the effects of reduced cholinergic tonus on socially motivated behaviour. Here, we evaluated the cholinergic system role in social memory and aggressive behaviour, through the administration of atropine, a muscarinic acetylcholine receptor antagonist, and by using genetically modified animals, the VAChT knockdown mice. These animals have expression of acetylcholine vesicular transporter (VAChT) reduced, then representing a model of cholinergic hypofunction. Our results demonstrated long-term social memory (LTSM) impairment in VAChT KDHET mice whose VAChT expression is around 50%. VAChT KDHOM, which expresses around 30% of VAChT protein, show short-term and longterm social memory deficits. The memory impairments of VAChT KD groups are not related to anxiety or reduced olfactory abilities, which were evaluated in the elevated plus-maze and buried food-finding test. We also demonstrated that the administration of atropine immediately after memory acquisition impaired its retention, thus suggesting that cholinergic signalling through muscarinic receptors is necessary to consolidation of LTSM. However, the acetylcholinesterase inhibitor fisostigmine, administered immediately after training, was not able to reverse LTSM impairment of VAChT KD mice. Our results indicate that reduced cholinergic tonus impairs the acquisition and the retention of LTSM. We also evaluated the effect of reduced cholinergic tonus on aggressive behaviour. VAChT KDHET and VAChT KDHOM mice are six and three times, respectively, more aggressive than VAChT WT mice. Furthermore, the number of attacks was higher in VAChT KDHET mice compared to VAChT WT mice. There are studies suggesting that acetylcholine may modulate vasopressin synthesis, and vasopressin seems to modulate socially motivated behaviours. Thus, we decided to evaluate the vasopressin participation on the agressive behaviour of VAChT KD mice. There was no difference between VAChT WT and VAChT KD mice regarding vasopressin immunoreactivity in the paraventricular nucleus. However, vasopressin administration was able to blockade the aggressive behaviour expression in VAChT KDHET mice. In addition, vasopressin also reduced the duration that VAChT KDHET mice spent investigating the intruder during the aggressive test. Taken together our results demonstrate that cholinergic tonus has an essential role on social information processing and also suggest a croos-talk between cholinergic and vasopressinergic systems in modulating aggressive behaviour, since decrease of cholinergic tonus produces an exacerbated aggressive behaviour, which is blockade by vasopressin administration